Semiparametric Estimates and Goodness-of-Fit Tests for Tire Wear and Failure Time Data - Levulienė, Rūta (Nonlinear Analysis: Modelling and Control, 2002)
The goodness-of-fit test for tire wear and failure time data with multiple failure modes is proposed. Parametric estimators of traumatic event cumulative intensities and semiparametric estimates of various reliability characteristics are given and their large sample properties are investigated. Real tire wear and failure time data are analyzed.